Financial Performance Islamic Banking: a Comparative Analysis Before and During the Covid-19 Pandemic in Indonesia - Candera, Mister; Indah, Karina Dwi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
The Covid 19 pandemic which spread to all countries in the world including Indonesia, caused various economic sectors, especially the financial sector, to be shaken. Especially at the beginning of the Covid 19 case, almost all sectors of the economy were paralyzed. Government regulations prohibiting non-essential activities outside the home, restricting operations in several vital sectors, and prohibiting crowds, add to the long list of causes for the weak performance of the financial sector. However, the Islamic banking financial sector was not too affected as evidenced by the financial performance of Islamic banking which was still in a good category. So it is necessary to further investigate the differences in the financial performance of Islamic banking before and during the Covid 19 pandemic in Indonesia. The data used in this study are secondary data collected through documentation. The number of samples studied was 34 Islamic banking consisting of 14 Islamic Commercial Banks and 20 Islamic Business Units. The data analysis used was the Multivariate Analysis of Variance (MANOVA) analysis. The results of the analysis show that there are differences in the financial performance of Islamic banking before and during the COVID-19 pandemic in Indonesia. In addition, before and during the Covid 19 pandemic had a significant effect on Islamic banking financial performance consisting of Non Performing Finance (NPF), Capital Adequacy Ratio (CAR), and Return On Assets (ROA).